2006
DOI: 10.1111/j.1365-2966.2006.10735.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating galaxy clusters - I. Thermal and chemical properties of the intracluster medium

Abstract: We have performed a series of N‐body/hydrodynamical (treesph) simulations of clusters and groups of galaxies, selected from a cosmological volume within a Lambda cold dark matter (ΛCDM) framework: these objects have been resimulated at higher resolution to z= 0, in order to follow also the dynamical, thermal and chemical input on to the intracluster medium (ICM) from stellar populations within galaxies. The simulations include metallicity‐dependent radiative cooling, star formation according to different initi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 164 publications
(275 reference statements)
9
73
0
Order By: Relevance
“…Valdarnini (2003) performed an extended set of cluster simulations and showed that profiles of the iron abundance are steeper than the observed ones. A similar analysis has been presented by Romeo et al (2006), who also considered the effect of varying the IMF and the feedback efficiency on the enrichment pattern of the ICM. Scannapieco et al (2005) presented an implementation of a model of chemical enrichment in the GADGET-2 code, coupled to a self-consistent model for star formation and feedback.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Valdarnini (2003) performed an extended set of cluster simulations and showed that profiles of the iron abundance are steeper than the observed ones. A similar analysis has been presented by Romeo et al (2006), who also considered the effect of varying the IMF and the feedback efficiency on the enrichment pattern of the ICM. Scannapieco et al (2005) presented an implementation of a model of chemical enrichment in the GADGET-2 code, coupled to a self-consistent model for star formation and feedback.…”
Section: Introductionmentioning
confidence: 77%
“…As an example, we show in the left panel of Fig. 8 the comparison between the iron profiles measured by De Grandi et al (2004) and results from the chemodynamical SPH simulations by Romeo et al (2006). These authors performed simulations for two clusters having sizes comparable to those of the Virgo and of the Coma cluster, respectively.…”
Section: Metallicity Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmological hydrodynamical simulations have been used with similar goals (Valdarnini 2003;Romeo et al 2006;Tornatore et al 2007;Davé et al 2008;Wiersma et al 2011;Crain et al 2013;Skory et al 2013): the results by Tornatore et al (2007) showed good agreement of metal abundances in simulated clusters in absence of AGN feedback at the price of significant over-production of galaxy stellar masses. More recent papers highlighted that much better agreement between stellar masses and cluster metallicities with observational results can be achieved when AGN feedback is included (Wiersma et al 2011;Crain et al 2013;Skory et al 2013).…”
Section: Comparison To Recent Simulationsmentioning
confidence: 99%
“…The history of theoretical studies of galaxy clusters is long and one of the approaches that has been followed by several authors to model these systems and to understand the origin of their metal content is through semi-analytical models coupled to N-body simulations (Cora et al 2008;Kapferer et al 2009;Arieli et al 2010;Short et al 2013) or cosmological hydrodynamical simulations (Valdarnini 2003;Romeo et al 2006;Tornatore et al 2007;Davé et al 2008;Wiersma et al 2011;Crain et al 2013;Skory et al 2013). Most state-of-the-art cosmological zoom-in simulations of galaxy clusters reach a spatial resolution of "kpc (Puchwein et al 2008;Teyssier et al 2011;Ettori et al 2012;Martizzi et al 2014b;Le Brun et al 2014;Lau et al 2015;Sembolini et al 2015).…”
Section: Introductionmentioning
confidence: 99%